P1039BARIATRIC SURGERY AND RISKS OF RENAL DISEASES, CARDIOVASCULAR DISEASES AND MORTALITY AMONG PATIENTS WITH TYPE 2 DIABETES MELLITUS. (6th June 2020) - Wong, Carlos; Wu, Tingting; Wong, Simon; Law, Betty; Grieve, Eleanor; Wu, Olivia; Lam, Cindy
Abstract: Background and Aims: To measure and compare the risks of end-stage renal diseases (ESRD), cardiovascular diseases (CVD), all-cause mortality between obese type 2 diabetes mellitus (T2DM) patients with and without bariatric surgery. Method: A retrospective population-based cohort of 1, 690 obese T2DM patients who were free of ESRD and CVD were assembled based on 2006-2017 Hospital Authority database. One-to-five propensity-score matching was used to balance baseline covariates between patients in bariatric surgery and control groups. Incidence rates (IR) of stage 4/5 chronic renal diseases, ESRD, CVD and all-cause mortality events for two groups were calculated. Hazard ratios (HR) for stage 4/5 chronic renal diseases, ESRD, CVD events were assessed using Cox proportional hazard models. Changes in estimated glomerular filtration rate (eGFR), and urine albumin-creatinine ratio (UACR) were measured up to 60 months. Results: Over a mean follow-up period of 34 months with 863 person-years, cumulative incidences of mortality, stage 4/5 chronic kidney diseases, ESRD and CVD for surgical patients were 0, 0.050, 0.017, and 0.036, respectively. Surgical patients had reduced IR of all-cause mortality, stage 4/5 chronic kidney diseases, ESRD and CVD (IR=0, 1.784, 0.587 and 1.321 per 100 person-years, respectively) than control patients (IR=1.954, 2.028, 0.914 and 2.814 per 100 person-years, respectively). Surgery group had a significant reduction in risk of CVD events (HR=0.464, P=0.015), and no occurrence of mortality events. However, the IR of stage 4/5 chronic kidney diseases and ESRD of the two groups were not significantly different. Surgical patients had significantly higher eGFR within 12 months, and had significantly lower until 48 months. Conclusion: Among obese T2DM patients, bariatric surgery lowered the risk of CVD and mortality, and was beneficial towards the kidney outcomes of eGFR up to 36 months.